Teaching Materials of Cluster Blended-Based Learning on Reduction-Oxidation Reactions to Improve Students’ Scientific Literacy - Arisy Erwin Junaidah; Erman Erman; Rahardjo Rahardjo (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
This study aims to describe the feasibility of teaching material (syllabus, Lesson Plans, Independent Learning Activity Unit and pretest-posttest question grid) of cluster-blended learning based on reduction oxidation reactions for grade X science high school chemistry learning. Validity, practicality and effectiveness were used to describe the teaching material’s feasibility. Data analysis of validity, practicality, and effectiveness results showed that. The teaching materials developed are eligible with a percentage of agreement more than 75%. Therefore, cluster-blended learning teaching materials are declared to meet the validity, practical, effectiveness criteria in high category. As implication, it is feasible to use as teaching materials of reduction oxidation reactions to improve students’ scientific literacy.